Experiências literárias na primeira infância: caminhos possíveis para a formação de professores - Fuertes, Silvia Helena Mihok (2017)
The main purpose of this research was to enlarge the discussion about the relevance of literary experiences in early childhood education and to detect what elements should be thoroughly studied, concerning literature reading in inservice teacher education. The source of the research problem were many readings and discussions promoted during the Professional Master Program and my job as pedagogic coordinator at a private school in Sao Paulo. The theoretical framework for teachers education was based on the ideas by Canario (1998), Imbernon (2009) and Alarcao (2011), and to discuss the relevance of literary experiences in teacher education, the inspiration came from Lerner’s work (2002), Reys (2010 and 2012), and Colomer (2007). To better answer the purpose of this research, we used a mixed questionnaire, composed by eight questions which was answered by the teacher in the school. Some of the questions intended to know better the teachers, their academic life and reading habits. The open questions invited the teachers to talk about their thoughts on reading and its relevance in the school, what is the right moment to read to the children and how to prepare for this moment, what are the criteria to choose the book and lastly what the children learn from teachers who read to them every day. To analyze the data, we used Andre’s discussions (1983) which suggests prose analysis as a way to better understand the content of teachers’ discourse. The first step was to analyze the collected data by locating the main topics, then the topics were grouped according similarities, frequency of occurrence and relevance. The topics were organized by themes which led to another step that was the building of categories which were inspired in the ideas by Colomer (2007), Reys (2010) and Lerner (2002). The categories are: the teacher and the relationship with reading; literary experiences and reading education, literary reading in schools as a permanent activity: story circle, literary reading and kids teaching. The findings revealed that teachers have much knowledge about the relevance of reading in early childhood education and that they believe that through reading is possible to develop reading behavior and to approach children to written culture, but it seems that there is a difficult in explaining how those knowledge are constructed by children. For this reason, it is proposed a continue teacher education project that would open new paths for reflection on practices and will expand teachers’ knowledges on how important is to promote good reading experiences for young children